LNC297 promotes BMSCs differentiation and alleviates BHBA-induced inhibition through the miR-145/GAS7 axis - Tao Tang; Jing Zhou; Xianbo Jia; Jiahao Shao; Meigui Wang; Siqi Xia; Shuai Chen; Wenqiang Sun; Jie Wang; Song-jia Lai (PLoS ONE, 2026)
Ketosis in dairy cows is characterized by elevated circulating β-hydroxybutyrate (BHBA) and profound alterations in whole-body energy metabolism. As a major peripheral tissue responsible for energy consumption and substrate utilization, skeletal muscle is continuously exposed to increased BHBA during ketosis and may use BHBA as an alternative energy substrate. However, the regulatory mechanism by which BHBA affects skeletal muscle differentiation remains unclear.This study used bovine skeletal muscle satellite cells (BMSCs) to investigate the effects of BHBA on the differentiation of BMSCs and to explore the regulatory roles of LNC297, miR-145, and GAS7 in this process. The results of dual-luciferase reporter gene assays and miRNA pull-down experiments verified the targeting relationship between LNC297, miR-145, and GAS7. BHBA inhibits the differentiation of BMSCs in a dose-dependent manner. Both LNC297 and GAS7 promote the differentiation of BMSCs and attenuate the inhibitory effect of BHBA. In contrast, miR-145 inhibits BMSCs differentiation and enhances the inhibitory effect of BHBA. Mechanistically, LNC297 acts as a competing endogenous RNA (ceRNA) or molecular sponge for miR-145, thereby upregulating GAS7 expression and promoting its differentiation function. LNC297 may promote muscle differentiation through the miR-145/GAS7 axis, thereby alleviating muscle damage in cows with ketosis, providing a new perspective for investigating the mechanisms of muscle development disorders.